Diagnóstico de gestores universitários por meio da metodologia de análise comportamental DISC profiler: estudo da gestão estratégica por competências - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Higher Education Institutions (HEIs) have used new management models to ensure good delivery of quality services to citizens. Competences Management (CM), based on provisions in applied legislation of the (NPDP) National People Development Plan, is a tool that has come to be used as a strategy for organizations, as well as using the DISC Profiler Analysis indicators. Profiler for the development of these individuals’ skills and abilities? There is little scientific production about CM, mainly in universities, however the need is imminent, with legal definitions by the Federal Government, even if there are still certain doubts about the process in its practical nature. This study aims to demonstrate the disclosure, based on the DISC Profiler Behavioral Profiler Analysis, of competencies and skills, and parameterization of criteria for taking advantage of the qualifications of university managers. This is a simple case study, carried out through qualitative, applied and exploratory research with the application of DISC Profiler Behavioral Profile Analysis in managers of a Federal Institute in the city of Ceres/GO in the year 2023. In addition, a verification and comparison of skills and abilities verified in behavioral analysis reports. Definitions of competencies are diverse and are closely linked to individuals' qualifications and abilities. From a better appreciation of human capital by organizations, the evolution of the theory of human behavior comes in handy with support for the planning strategy and possible implementation.
Diagnosis of university managers using the DISC profiler behavioral analysis methodology: study of strategic competencies management
Keywords: Gestão por competências; Habilidades; Perfil Comportamental; Universidade; Behavioral Profile; Management by competences; Skills; University; CIENCIAS SOCIAIS APLICADAS